Evaluation of Circular Aperture Transmission Coefficients in the Presence Of Obscurations - Davis, J. G.; Shakespeare, P.; Kiley, N. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper describes a novel parametric approach to the simulation of circular aperture transfer functions in the presence of obscurations at microwave frequencies. A novel virtual ‘absorbing box’ power loss integration technique is applied to successfully demonstrate its validity for conditions where the aperture diameter approaches one tenth of the plate largest dimension.